Analisis the Update D&M IS Success Model Pada Penerapan Sistem Informasi Pemerintahan Daerah (SIPD) pada Kota Sawahlunto - Hukmi, Wilda; Rahayu, Rita (Jurnal Informatika Ekonomi Bisnis, 2023)
Information technology is growing rapidly not only in the private sector but also by government agencies.The ministry of home affairs regulates a system that is connected and integrated in one system, namely SIPD. By using D&M IS Success Model-based approaches, this paper investigate the success of SIPD. Testing using PLS were applied to data collected by a questionnaire from 93 employees from each OPD in Sawahlunto. In this study, empirically evaluated the model for measuring the success of SIPD of constructs from the updates Delone and Mclean IS Success Model. Four out nine hypothesized relationships between six success variables are significantly supported. The findings of this study can be used to asses the success of SIPD from standpoint of the government employees.